Tendencies in Tomosynthesis Research Output 2000-2020: Bibliometric Analysis - Kumar, Kutty; Pitla, Raja Suresh Kumar (Journal of Data Science, Informetrics, and Citation Studies)
Mammography has reached near-universal adoption because of the established capabilities in detecting and diagnosing breast cancer. In addition to first being used in radiology, digital imaging has significantly impacted tomographic imaging. Future applications of this breast tomosynthesis technique may result in its usage instead of mammography for breast cancer screening. An in-depth discussion of the long-term development of breast tomosynthesis is presented in two papers. This imaging modality emphasizes medical physics elements that Research tends to focus on. This first paper will discuss the previously conducted Research in system design, geometry, and technique optimization when acquiring images, including scattering from X-rays and radiation dose. A companion paper on breast tomosynthesis imaging techniques will present an overview of the reconstruction process.
Keywords: Tomosynthesis; Publications; Bibliometric; VOSViewer; Sankey.